Checkpoint Inhibitor-Associated Scleroderma and Scleroderma Mimics - Michael Macklin; Sudeep Yadav; Reem Jan; Pankti Reid (MDPI AG, 2023)
Immune checkpoint inhibitors (ICI) are the standard of care for various malignancies and have been associated with a wide spectrum of complications that are phenotypically akin to primary autoimmune diseases. While the literature on these toxicities is growing, there is a paucity of data regarding ICI-associated scleroderma which can carry significant morbidity and limit the ability to continue effective ICI therapy. Our review aimed to analyze the current literature on ICI-associated systemic scleroderma (ICI-SSc) and key scleroderma mimics. Cases of ICI-SSc had notable differences from primary SSc, such as fewer vascular features and less seropositivity (such as scleroderma-specific antibodies and antinuclear antibodies). We found that patients with a diagnosis of SSc prior to the start of ICI can also experience flares of pre-existing disease after ICI treatment used for their cancer. Regarding scleroderma mimics, several cases of ICI-eosinophilic fasciitis have also been described with variable clinical presentations and courses. We found no cases of scleroderma mimics: ICI-scleromyxedema or ICI-scleroedema. There is a critical need for multi-institutional efforts to collaborate on developing a patient database and conducting robust, prospective research on ICI-scleroderma. This will ultimately facilitate more effective clinical evaluations and management for ICI-scleroderma.